Preadjusted edgewise fixed orthodontic appliances : principles and practice - Naini, Farhad B.; Gill, Daljit S. (Hoboken, NJ : John Wiley and Sons, Incorporated, 2022)
'Explore the possibilities of preadjusted edgewise appliances in orthodontics with this essential resource Preadjusted Edgewise Fixed Orthodontic Appliances: Principles and Practice comprehensively covers the increasingly popular preadjusted edgewise technique in orthodontics. The book integrates clinical practice and research findings, focusing on the biomechanics and clinical management of patients with preadjusted edgewise appliances. A unique learning resource for specialists and trainees in orthodontics, the book is highly illustrated and broad in scope, covering everything from informed patient consent to clinical techniques to information about how to manage patient malocclusions. Core topics include: A thorough introduction to the principles of treatment planning, orthodontic biomechanics, anchorage, informed patient consent, and the dentolegal aspects of orthodontic treatment ; An exploration of the preadjusted edgewise appliance, including bracket design, bracket placement, orthodontic bonding and debonding, archwires, mini-implants (TADs) and auxiliaries; Comprehensive description of the stages of treatment with preadjusted edgewise appliances, including alignment and levelling, controlled space closure, finishing and retention Information on the management of the major malocclusions (Class II, Class III, anterior open bite, deep overbite and transverse problems) with preadjusted edgewise appliances Perfect for postgraduate dentists undergoing specialist training in orthodontics, specialist practitioners, and hospital consultant orthodontists, Preadjusted Edgewise Fixed Orthodontic Appliances: Principles and Practice will also be useful to dentists with a special interest in orthodontics, orthodontic therapists, and orthodontic nurses who seek a comprehensive manual of the most popular fixed orthodontic appliance technique'--Provided by publisher.
Principles of Treatment Planning / Farhad B. Naini and Daljit S. Gill -- Principles of Orthodontic Biomechanics / Farhad B. Naini and Daljit S. Gill -- Anchorage / Zaid B. Al-Bitar -- Consent / Gavin J. Mack -- Dentolegal aspects of orthodontic treatment / Alison Williams -- Bracket Design / Chris D. Donaldson -- Bracket Placement / Hemendranath V. Shah, Daljit S. Gill and Farhad B. Naini -- Bonding in Orthodontics / Declan Millett -- Debonding / Lucy Davenport Jones -- Archwires / Leila Khamashta-Ledezma -- Auxiliaries / Andrew T. DiBiase and Jonathan Sandler -- Mini-implants (TADs) / Richard R. J. Cousley -- Care of fixed appliances / Nazan Adali, Daljit S. Gill and Farhad B. Naini -- Stages of Treatment with Preadjusted Edgewise Appliances -- Alignment and Levelling / Farhad B. Naini and Daljit S. Gill -- Controlled Space Closure / Daljit S. Gill and Farhad B. Naini -- Finishing / Mohammed Owaise Sharif and Stephen M. Chadwick -- Retention / Simon J. Littlewood -- Management of Class II malocclusions / Martyn T. Cobourne and Mithran S. Goonewardene -- Management of Class III malocclusions / Grant T. McIntyre -- Management of Deep Incisor Overbite / Farhad B. Naini, Daljit S. Gill and Umberto Garagiola -- Management of Anterior Open Bite / Chung How Kau and Tim S. Trulove -- Management of the Transverse Dimension / Lucy Davenport-Jones.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 31, 2022).
Keywords: Orthodontic Appliances, Fixed; Orthodontic Appliances